Uji Kemampuan Serbuk Daun Jambu Biji (Psidium guajava L.) dalam Mengendalikan Penyakit Antraknosa pada Tanaman Terung (Solanum melongena L.) - Misda Misda; Dewi Fitriyanti; Yusriadi Marsuni (JURNAL PROTEKSI TANAMAN TROPIKA, 2023)
This study aims to determine the ability of guava leaf powder (P. guajava L.) in controlling anthracnose disease caused by the fungus Colletotrichum sp. on eggplant (S. melongena L.). This research was conducted in March – July 2022. This study used a Completely Randomized Design (CRD) which consisted of 6 treatments, each treatment was repeated 4 times so that there were 24 treatment units and each replicate consisted of 5 plants, so a total of 120 plants . The treatments used were 0, 20, 25, 30, 35 and 40 g of guava leaf powder + 100 ml of distilled water. Based on the observed concentration of 25 g of guava leaf powder + 100 ml of distilled water (T2) it has the longest incubation period of 11.74 days with disease incidence and disease intensity of 18.49% and 3.66%, respectively